Asperger syndrome, adolescence and identity : looking beyond the label - Molloy, Harvey, 1961- (Jessica Kingsley Publishers, 2004)
Annotation "How do teenagers with Asperger Syndrome view themselves and their own lives? This book is based on extensive interviews with adolescents diagnosed with AS. It includes six life stories, written in collaboration with the teenagers themselves. These present an authentic and fascinating look at the lives of the teenagers and how AS has shaped their growing identities. The stories provide the basis for a discussion of common themes and issues facing teenagers with AS. Asperger Syndrome, Adolescence, and Identity also questions the medicalized deficit approach to Asperger Syndrome and discusses the social repercussions of labeling teenagers as having AS."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.